Analisis Pengaruh Tata Kelola Perusahaan Terhadap Nilai Perusahaan Melalui Variabel Intermediasi Berupa Struktur Modal Pada Perusahaan BUMN - Mohamad Bastomi (eCo-Buss, 2021)
This study aims to provide empirical evidence the effect of corporate governance on firm value, either directly or indirectly through the mediating variable in the form of capital structure. The sample used is based on the purposive sampling method so that there are 12 state-owned companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The data were analyzed using Partial Least Square (PLS) as a hypothesis testing tool and using the software Free Statistic Calculation for Sobel Test version 4 to test the mediating variables. This study shows empirical evidence that corporate governance has a significant effect on capital structure, capital structure has a significant effect on firm value, and corporate governance has a significant effect on firm value, either directly or indirectly through capital structure as a mediator variable.